Effect of tooth enamel staining by coffee consumption during at-home tooth bleaching with carbamide peroxide - João Victor Frazão CÂMARA; Luine de Paiva Pereira Santos de SOUZA; Daniel Otero Amaral VARGAS; Isabel Ferreira BARBOSA; Gisele Damiana da Silveira PEREIRA (Universidade Estadual Paulista, 2020)
Abstract Introduction Obtaining the result expected during tooth bleaching requires a correct diagnosis of the type of staining presented. The causes of tooth staining differ depending on the etiological factor. Objective To assess the color change caused by the immersion of bovine teeth in coffee solution during at-home tooth bleaching using a 16% carbamide peroxide gel. Material and method Thirty-three sound bovine teeth were assigned to three groups of eleven teeth each: 1 - Teeth bleached (TB) four hours per day for 21 days; 2 - TB four hours per day for 21 days and immersed in coffee solution immediately after tooth bleaching; 3 - TB four hours per day for 21 days and immersed in coffee solution four hours after the end of tooth bleaching. Immersed in coffee was performed for 15 minutes and tooth color was assessed before the start of the bleaching procedure and after 21 days with an intraoral spectrophotometer. Test Shapiro-Wilk was used to assess homoscedasticity and data were submitted to one-factor Analysis of Variance (ANOVA) and Tukey's test (p <0.05). Result The color change observed in group 1 (5.76 ± 2.74)A was not statistically different from group 2 (8.83 ±5.11)A, which was immersed in coffee solution immediately after tooth bleaching, and from group 3, which was immersed in coffee solution four hours after tooth bleaching (8.20 ±3.71)A. Conclusion Coffee did not interfere with the tooth bleaching results, regardless of the time after the procedure. Hence, diet restrictions are not necessary during tooth bleaching.